Procedural bread making - Baravalle, Rodrigo Guillermo (2015)
Accurate modeling and rendering of food, and in particular of bread and other baked edible stuff, have not received as much attention as other materials in the photorealistic rendering literature. In particular, bread turns out to be a structurally complex material, and the eye is very precise in spotting improper models, making adequate bread modeling a difficult task. In this paper we present an accurate computational bread making model that allows us to faithfully represent the geometrical structure and the appearance of bread through its making process. This is achieved by a careful simulation of the conditions during proving and baking to get realistically looking bread. Our results are successfully compared to real bread by both visual inspection and by a multifractal-based error metric.